50 Serum Antigen Testing for Initial Histoplasmosis Detection Is Usually Unnecessary If Urinary Antigen Testing Is Performed. (11th January 2018) - Libert, Diane; Ansari, Mohammad; Procop, Gary
Abstract: Introduction: Histoplasma capsulatum is a fungus endemic to the Ohio and Mississippi River valleys that can cause pulmonary illness or disseminated infection. There are several tests for histoplasmosis, but serum and urine antigen (UAg, SAg) detection by enzyme-linked immunosorbent assay (ELISA) is most commonly performed due to its speed and accuracy. Studies have shown that UAg detection has higher sensitivity than SAg detection. Methods: At our hospital, UAg detection alone is usually ordered as an initial screen. However, SAg detection is ordered instead or in addition to UAg detection in some instances. The goal of this retrospective analysis was to determine whether SAg detection plays a useful role in the initial evaluation of a patient with suspected histoplasmosis. Results: From 1997–2016, 20, 285 UAg and 1, 426 SAg tests were performed. From this data, we collected results from pairs of UAg and SAg tests completed on a patient within the same week (ie, paired specimens). Of 615 total paired specimens, 555 were concurrent negatives and 49 were concurrent positives, yielding 98% agreement between UAg and SAg detection. Eight of the 11 remaining paired specimens with discrepant UAg/SAg findings had available medical records. Based on infectious disease consult notes, culture data, and other patient data, we assigned six cases of UAg false positivity, one case of true positivity, and one case of false negativity. Conclusion: In the context of other studies, these findings support the use of UAg detection alone when first testing for suspected histoplasmosis. This aligns with the current practice of most physicians. Furthermore, this study indicates that SAg detection should be performed when a positive UAg result warrants confirmation, rather than as part of an initial screen.